The influence of TiC nanoparticles addition on the microstructure and mechanical properties of IN738LC alloy prepared by EB-PBF - Wei Wei; Yang Li; Bo Wei; Yuemei Tan; Pengcheng Lv; Pengxiang Nie; Yurong Wang; Xiaoyu Liang; Ting Long; Jun Zhou; Feng Lin (Materials & Design)
The addition of nano reinforcement particles to improve the mechanical properties of nickel-based superalloys in additive manufacturing has become a current research focus. This paper systematically investigates the effects of adding 1.0 wt% TiC nanoparticles on the microstructure and tensile properties of nickel-based superalloy (IN738LC) prepared by electron beam powder bed fusion (EB-PBF). The results show that the adding of TiC nanoparticles promotes the nucleation of new grains while inhibiting the growth of the original grains, reducing the grain width from 82.09 μm to 28.55 μm. After the addition of TiC, the average size of the secondary γ′ phase decreased by 73.2 %, while the average size of the primary γ′ phase increased by 114.2 %, and the overall amount of γ′ phase increased by 80.6 %. In addition, the average size of MC carbides increased by 17.16 %, and their quantity increased by 96.2 %. At room temperature, the ultimate tensile strength and elongation at fracture of the composite (1.0 wt% TiC/IN738LC) improved by 23 % and 77 %, respectively. Post-tensile testing, the composite exhibited more and larger dimples, with more carbides within the dimples, thus enhancing the alloy’s ductility. The strengthening mechanism of the primary γ′ phase mainly relies on dislocation pile-up and bypassing, improving the material’s strength; the secondary γ′ phase primarily enhances ductility through dislocation cutting. MC carbides cause more dislocation pile-up, further improving the alloy’s resistance to deformation. This paper provides new insights for the development of high-performance nickel-based superalloys.